Aquatic Oligochaeta (Annalida:Clitellata) as Bio Indication for Sediment Quality Assessment in Tigris River Within Baghdad City /Iraq (Baghdad Science Journal, 2021)
Aquatic Oligochaeta is an important group of Macroinvertebrates that has been very remarkable as bioindicators for assessing water pollution and determining its degree in water bodies. Hence, the idea of the current study aims at studying the impact of Baghdad effluents on the Tigris River by using oligochaetes community as bioindicators . For this purpose, four sites along the inside of Baghdad has been chosen. Site S1 has been located upstream, site S2 and S3 has been at midstream and site S4 at the downstream of the River.This investigation has used different types of biological indicators, including the  percentage of oligochaeta  within benthic invertebrates, which ranged from 49.2-51.28%. The highest percentage of the tubificid worms in the benthic samples has been 26.95% and recorded at S4, while the lowest percentage has been 14.45% recorded at S1. Pollution index D ranged between 0.34 and 0.52. The highest value of the ratio of  oligochaeta to Chironomidae larvae has been 3.5 recorded at S4, while the lowest value has been 2.6 reported at S1. The percentage of L. hoffmeisteri within the oligochaetes community has been from 35-56%.  The highest value of  biological quality index Io has been   9.89  recorded at S1, and the lowest value has been (5.57)  recorded in S4.  A Composite index of Biological quality  (Eo) index recorded as C5 in S1 and C4,D3 and E3 in the other sites.  Oligochaeta index of sediment bioindication (IOBS) values ranged between 2.55 at S1 and 1.15 at S4. The tubicid index of sediment TUSP reported at d the highest value (52.57%) at  S4 where as the lowest value has been 28.68% at S1. The highest species richness value has been 7.35  recorded at S1 and the lowest value has been 6.12 at S3. Shannon- Weiner diversity index (H) ranged from 0.06-0.049 Bit/ind. Species uniformity index (E) has been 0.018-0.016.It is clear from the results that most of the biological indices indicate that the Tigris River sediment has been slightly impacted by anthropogenic activity during its passage through the Capital Baghdad.  S1 is considered as a reference site, as it has presented the first point of entry of the Tigris River to Baghdad and then the sediment gradually  has become polluted to reach its highest degree in  the last site S4 after passing through several  slightly polluted sites.